A blade-coated highly efficient thick active layer for non-fullerene organic solar cells. Issue 39 (30th September 2019) - Zhang, Lin; Zhao, Heng; Lin, Baojun; Yuan, Jian; Xu, Xianbin; Wu, Jingnan; Zhou, Ke; Guo, Xia; Zhang, Maojie; Ma, Wei
Abstract : Highly efficient large-area thick-film organic solar cells were fabricated by blade-coating with finely controlling the molecular packing. Abstract : Regulating molecular ordering and nanoscale morphology of photoactive layer is crucial to achieve high carrier mobility for fabricating thick-film organic solar cells (OSCs). Herein, molecular ordering and phase separation were finely controlled by varying the substrate temperature in blade-coated PM6:IT-4F devices. The blade-coated devices with low substrate temperature (30 °C) show low crystallinity of IT-4F and poor device performance. However, a high power conversion efficiency (PCE) of 13.64% was achieved for the device blade-coated at 50 °C in air without any other processing treatments, due to the well-ordered molecular packing along the backbone direction of IT-4F molecules. When the film thickness increased to 400 nm, an excellent PCE of 10.22% was achieved in the device blade-coated at 70 °C, which is higher than that of the optimal device blade-coated at 50 °C. This was attributed to the much improved crystallinity within the long-range ordered side-chain packing of IT-4F molecules and the newly emerged small-scale phase separation providing purer domains and continuous charge transport channels. Furthermore, large-area (90 mm 2 ) devices exhibit high PCEs of 11.39% and 9.76% with a 56 mm 2 aperture at film thicknesses of 135 nm and 306 nm, respectively. In addition, the device blade-coated at 70 °C exhibits good storage stability. This work provides comprehensive guidance for optimizing the molecular ordering and nanoscale morphology to fabricate high-efficiency thick-film OSCs.